2021
DOI: 10.1080/2331186x.2021.1921903
|View full text |Cite
|
Sign up to set email alerts
|

Exploring assessment across cultures: Teachers’ approaches to assessment in the U.S., China, and Canada

Abstract: Classroom assessment dynamics are shaped by individual and local understandings of assessment (assessment micro-cultures), as well as common assessment beliefs and practices that stem from system-wide features, such as large-scale testing (assessment macro-cultures). Teachers' approaches to assessment reveal how they navigate assessment micro-and macro-cultures to support student learning and achievement. Despite increasing migration of students between the U.S., China, and Canada, little research has examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 76 publications
(121 reference statements)
1
2
0
1
Order By: Relevance
“…In this study we observed PPL grow as an assessor over the course of a semester as she drew upon her assessment knowledge and the collective assessment literacy of a community of practice. This observation supports the suggestions by Looney et al (2018) andDeLuca et al (2021), that instructors' beliefs and their cultural context are important elements of teacher assessor identity. PPL engaged in the biochemistry CoP, which was specifically developed to build pedagogical support for threshold concepts, including PBI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study we observed PPL grow as an assessor over the course of a semester as she drew upon her assessment knowledge and the collective assessment literacy of a community of practice. This observation supports the suggestions by Looney et al (2018) andDeLuca et al (2021), that instructors' beliefs and their cultural context are important elements of teacher assessor identity. PPL engaged in the biochemistry CoP, which was specifically developed to build pedagogical support for threshold concepts, including PBI.…”
Section: Discussionsupporting
confidence: 90%
“…By extension, to create relevant professional development opportunities, it is important to examine the assessment assets that instructors bring and enact in their teaching practice in order to create relevant professional development opportunities. Instructor assets include analytical skills, content knowledge, socio-cultural knowledge, and experiences (Mansour, 2009;Harper, 2010;Samuelson and Litzler, 2016;Cowie and Trevethan, 2021;Abell and Sevian, 2021;DeLuca et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…How he conducted formative assessment indicated that he carried out classroom assessment irrelevantly with his understanding. Ideally, he implemented classroom assessments inline with their understanding [24]- [26].…”
Section: Discussionmentioning
confidence: 99%
“…Teaching, learning, and assessment are the three interwoven components of a teaching and learning process (DeLuca et al, 2021;Wiliam, 2011). Educators undertake assessment to continuously examine the process, progress, and development of students' learning outcomes (Tharwat, 2018).…”
Section: Introductionmentioning
confidence: 99%